DIGITAL TECHNOLOGIES IN ONLINE ENGLISH CLASS FOR RAILWAY MECHANICAL STUDENTS DURING COVID19 OUTBREAK - Isti Pratiwi, Damar (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2021)
Online learning has opened many innovations and opportunities in developing digital technologies in classroom, especially in language learning. However, in English for Specific Purpose (ESP) like in Railway Mechanical Technology study program, the development of online applications is still limited. Therefore, there is an urgency to conduct study about digital technologies in English class for Railway Mechanical Technology. This study is aimed to describe instructional design of general English course for Railway Mechanical Technology and investigate the learning outcomes of general English course utilizing digital technologies. The data were collected during 2nd semester of 2020/2021 academic year (March – August) in Railway Mechanical Technology study program. There were 24 students participated in this study (91.67% male and 8.33% female). The data were analyzed using Paired-sample t-test, Pearson r correlation, and Spearman rho correlation. The results showed the significant improvement in online English class for Railway Mechanical Technology. Despite the correlation showed linier direction between pretest and posttest, the degree of correlation was low with weak entailment.These results shed light on course design utilizing digital technologies in general English course for Railway Mechanical Technology study program.